Structural integrity analysis of pipelines with interacting corrosion defects by multiphysics modeling. (March 2019) - Soares, Elder; Bruère, Vivianne Marie; Afonso, Silvana M.B.; Willmersdorf, Ramiro B.; Lyra, Paulo R.M.; Bouchonneau, Nadège
Abstract: To assess the structural integrity of pipelines with corrosion defects for transportation of petroleum, several methods can be applied. The Semi-Empirical Analytical Methods, although usually providing very conservative results, which results in premature shutdown of the lines, are still widely used as they generate quickly reliable results. The Finite Element Method (FEM) represents an alternative and has generated results with excellent accuracy when compared to results of experimental tests. Moreover, in the assessment of pipes transporting high temperature fluids under pressure, it becomes increasingly necessary to take into account the coupled thermo-mechanical phenomena. Therefore, this work aims to study the integrity of pipes with interacting corrosion defects under combined load composed by internal pressure and thermal loads using the FEM to show the importance of considering the thermal effects when evaluating the integrity of corroded pipes. At the end of the analyses, it was found that thermal loads can significantly reduce the failure pressure of corroded pipelines, with a percentage losses of up to 8.86% when a temperature of 125 °C is applied. Finally it was shown that the consideration of these loads greatly influences the structural integrity of corroded pipes, particularly for those with long total length and/or deep corrosion defects. Highlights: The FEM was used to accurately predict the failure pressure of corroded pipes. Multiphysics simulations show that thermal loads have a significant influence on the failure pressures of the corroded pipes. Thermal load has a greater impact on pipes with deeper and/or larger total length defects.